PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI PUSKESMAS SEI MENCIRIM DI MASA PANDEMIC COVID 19 - Esra Marolop Doloksaribu; Evawani Martalena Silitonga; Donal Nababan; Mindo Tua Siagian (Universitas Pahlawan, 2021)
Continuous improvement of service quality is one of the important keys in facing the era of globalization which implies that services must be carried out according to standards and meet quality rules that are oriented to the interests of consumers. With these programs and facilities, it is hoped that the community will no longer be reluctant to seek treatment at the Puskesmas. The purpose of this study was to analyze the effect of the quality of health services on the satisfaction of inpatients at the Sei Mencirim Health Center.This research is a survey research, conducted at the Sei Mencirim Health Center. The population was all patients who were hospitalized at the Sei Menistrim Health Center in January-July 2021 totaling 74 people and the entire population was taken as a sample. Primary data obtained from interviews and secondary data in the form of inpatient data. The hypothesis was tested using the Multiple Regression test.Based on Bivariate analysis revealed that there was no effect of physical evidence on patient satisfaction. There is an effect of reliability, responsiveness, assurance and empathy on patient satisfaction.The most dominant variable affecting patient satisfaction is empathy. Considering that empathy is the dominant variable affecting patient satisfaction, puskesmas need to improve quality individual service and patient family time for consultation is met.Keywords: Service Quality, Patient Satisfaction, Puskesmas Sei Mencirim